2007
DOI: 10.1177/1046878106297879
|View full text |Cite
|
Sign up to set email alerts
|

Symposium article: Simulation-based L2 writing instruction: Enhancement through genre analysis

Abstract: Researchers have highlighted various benefits of the simulation-based approach to second language (L2) writing instruction. In this article, the author argues, with specific pedagogical scenarios, that an explicit focus on genre and genre analysis in simulation-based L2 writing instruction can further enhance learners' reading of content materials, heighten students' awareness of discipline-specific generic features, and develop their discourse competence and writing accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the 1970s and for the most of the 1980s, experts were primarily interested in the process approach which focuses on developing students' linguistic skills through pre-writing activities such as planning, drafting, editing and revising (Badger & White, 2000;Feez, 2002;Muncie, 2002). In the late 1980s and the 1990s, however, theoretical interest in writing instruction shifted to a genre approach that considers writing as a purposeful act and focuses on the analysis of the contextual situation in which writing takes place (Atkinson, 2003;Cheng, 2006Cheng, , 2007Cheng, , 2008Hyland, 2003aHyland, , 2003bHyland, , 2007Johns, 2003;Paltridge, 1996Paltridge, , 2000Paltridge, , 2002Paltridge, , 2007Swami, 2008). The genre approach was developed in response to the criticism of the limitations of the process approach, which left students to find the recurring text structures for themselves through experimentation and exploration.…”
Section: Why Choose a Genre Approach?mentioning
confidence: 99%
“…In the 1970s and for the most of the 1980s, experts were primarily interested in the process approach which focuses on developing students' linguistic skills through pre-writing activities such as planning, drafting, editing and revising (Badger & White, 2000;Feez, 2002;Muncie, 2002). In the late 1980s and the 1990s, however, theoretical interest in writing instruction shifted to a genre approach that considers writing as a purposeful act and focuses on the analysis of the contextual situation in which writing takes place (Atkinson, 2003;Cheng, 2006Cheng, , 2007Cheng, , 2008Hyland, 2003aHyland, , 2003bHyland, , 2007Johns, 2003;Paltridge, 1996Paltridge, , 2000Paltridge, , 2002Paltridge, , 2007Swami, 2008). The genre approach was developed in response to the criticism of the limitations of the process approach, which left students to find the recurring text structures for themselves through experimentation and exploration.…”
Section: Why Choose a Genre Approach?mentioning
confidence: 99%
“…Nevertheless, in previous academic years, we had piloted the same study and had found similar results. Consequently, we might claim, as in [31][32][33] and [5], that a genre-based approach proves to be beneficial for graduate students' gains in academic literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In Anglophone academic contexts, in recent years, there have been a number of studies that have dealt with building genre awareness [5,[27][28][29][30][31][32][33][34], the effects of genre instruction [35,36], genre knowledge recontextualization [30,37], and approaches to genre tasks in diverse disciplines [38]. In addition, others have looked into academic biliteracy; e.g., Martin Martin [39], Gentil [40], Canagarajah [41], Mein [42], and Pérez-Llantada [43].…”
Section: Introductionmentioning
confidence: 99%
“…The use of simulation and gaming for instructional purposes has been widely applied in diverse disciplines since the mid twentieth century [7], [8]. Although the original definition of simulation has evolved over the decades, in essence it still refers to as a series of contextrich learner-centered tasks in which the participants embody well-defined roles.…”
Section: Introductionmentioning
confidence: 99%